Pupil trajectory tracing from video-oculography with a new definition of pupil location. (January 2023) - Deng, Weike; Huang, Jingru; Kong, Sheng; Zhan, Yinwei; Lv, Jujian; Cui, Yong
Abstract: Pupil localization is the critical technology of eye tracking, which plays a significant role in many eye movement analysis applications, such as pupil trajectory tracing from video-oculography(VOG). However, when the pupil is occluded, the existing representative pupil center based localization methods are imprecise or even unable to find the pupil. Unfortunately, in actual VOG, the pupil is inevitably covered by the upper eyelid, resulting in a poor effect of these approaches in practice. In order to alleviate this drawback, we initiate a new way to determine the pupil position by locating the lower pole of pupil (LLPP), which can accurately locate the pupil with about 5% of the exposed area. As a result, the proposed method can reduce locating mistakes, increase data utilization, and maintain pupil trajectories continuity. The experimental results in real VOG of the benign paroxysmal positional vertigo (BPPV) patients demonstrate the effectiveness and superiority of the proposed LLPP. Highlights: A new definition of pupil trajectory tracking in video-oculography is proposed. We proposed to use the lower pole of pupil as the location point. We designed an adaptive threshold method to segment the pupil. We manually annotated the actual BPPV inspection data set as experimental data. The proposed method shows good locating accuracy compared to its peer methodologies.